The Effect of Sustainability Report on Firm Value: Moderation of Good Corporate Governance - Asshiyami, Farichatun Nisa’; Putikadea, Insyirah (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the effect of sustainability report disclosure on firm value in the consumer non-cyclicals sector, with Good Corporate Governance (GCG) proxied by independent commissioners as a moderating variable. This study uses a quantitative approach with a causality research design. The population includes all consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Through purposive sampling technique, a sample of 21 companies with a total of 105 observations was obtained. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The results show that the sustainability report has a positive and significant effect on firm value, which is in line with signaling theory. GCG is also proven to have a positive effect on firm value. Furthermore, the MRA test proves that GCG significantly moderates the relationship between the sustainability report and firm value with a negative moderation direction (quasi moderation). This indicates a substitution effect, where strong governance oversight can replace part of the sustainability report's function in building trust and positive perceptions from capital market investors.